A Survey of Rare and Endangered Dicotyledonous Wild Plants - Nisreen Sabbar Hashim; Ghofran Ali Hussein; Hisham Tawfiq Jameel; Kian Sabbar Hashim; Omar Mohammed Shadhan (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Biodiversity loss is accelerating worldwide, with wild plants particularly vulnerable to climate change, urban expansion, and unsustainable exploitation. Specific background: In Iraq, especially Diyala Province, the scarcity of studies on rare and endangered dicotyledonous plants limits conservation planning and sustainable use. Knowledge gap: Despite the ecological and socio-economic importance of these plants, systematic documentation of their taxonomy, distribution, and local uses remains insufficient. Aims: This study aimed to conduct a comprehensive field survey to identify, classify, and assess rare and endangered dicotyledonous plants across Diyala Province. Results: Over three years (2021–2023), 300 species from 176 genera and 45 families were collected; among them, 20 rare and highly threatened species belonging to 19 genera and 10 families were recorded, with documentation of their growth forms, geographic distribution, and multiple local uses. Novelty: This is the first extensive, seasonally based survey providing detailed taxonomic classification and ethnobotanical insights into rare wild dicotyledons in Diyala. Implications: The findings highlight the urgent need for conservation measures to sustain plant biodiversity, safeguard genetic resources, and ensure continued ecological and community benefits. Highlights: Comprehensive survey of 300 wild dicotyledonous species across Diyala. Identification of 20 rare and threatened species with documented uses. First detailed seasonal assessment supporting biodiversity conservation. Keywords: Rare plants, Endangered species, Biodiversity, Conservation